Cultural approaches to studying religion: an introduction to theories and methods - Minister, M. Cooper; Bloesch, Sarah J. (Bloomsbury Academic, 2024)
"Introduces twelve of the most influential theories of the late 20th and early 21st centuries in the study of religion in one volume"--